1996
DOI: 10.1097/00005537-199606000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Assessment of Qualitative Olfactory Dysfunction in Different Age Groups

Abstract: The prevalence of parosmia and phantosmia among 363 chemosensory and nasal/sinus patients was studied, as was the accuracy with which our clinical questionnaire could assess these dysfunctions. We then investigated whether patients with parosmia or phantosmia, matched for odor intensity, perform poorer on odor identification than do patients with no dysosmia. More than 40% of the study group evidenced either parosmia (18.7%) and/or phantosmia (25.6%), a finding that suggests that more attention should be paid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
1
6

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 31 publications
1
61
1
6
Order By: Relevance
“…Altogether, 24% of the patients were diagnosed with parosmia and 11% with phantosmia. These percentages can be compared with 19% and 26% [19], and 12% and 4% [21] reported elsewhere. It is obvious that the prevalence of qualitative olfactory disorders reported from different olfactory clinics differs considerably.…”
Section: Discussionmentioning
confidence: 79%
“…Altogether, 24% of the patients were diagnosed with parosmia and 11% with phantosmia. These percentages can be compared with 19% and 26% [19], and 12% and 4% [21] reported elsewhere. It is obvious that the prevalence of qualitative olfactory disorders reported from different olfactory clinics differs considerably.…”
Section: Discussionmentioning
confidence: 79%
“…A decade ago [30], 16 patients diagnosed with questionable dementia (QD)-a similar, but more broadly defined, diagnostic class that preceded MCI-and 16 control subjects were administered odor threshold and odor recognition tasks. Significant differences were found between the two groups on both tasks.…”
Section: Olfactory Dysfunction Predicts Risk Of Incipient Dementiamentioning
confidence: 99%
“…Although substantial numbers of human studies have suggested that functional olfactory deficits increase with age and age-related illnesses (see, e.g., Schiffman, 1979;Schiffman and Leffingwell, 1981;Perl et al, 1992;Ship and Weiffenbach, 1993;Nordin et al, 1996;Moberg and Raz, 1997;Hoffman et al, 1998;Hummel et al, 1998;Larsson and Backman, 1998;Murphy et al, 1998;Geisler et al, 1999;Lehrner et al, 1999;Rolls, 1999), relatively little work has described the normal aging process in animal models. Research from one laboratory (Hinds and McNelly, 1977, 1979Kaplan et al, 1985) suggests large age-related changes in rats from 3 to 36 months.…”
mentioning
confidence: 99%